1978
DOI: 10.1021/bi00599a008
|View full text |Cite
|
Sign up to set email alerts
|

Properties and reaction mechanism of the bioluminescence system of the deep-sea shrimp Oplophorus gracilorostris

Abstract: The bioluminescent reaction of Oplophorus takes place when the oxidation of coelenterazine (the luciferin) with molecular oxygen is catalyzed by Oplophorus luciferase, resulting in light of maximum intensity at 462 nm and the products CO2 and coelenteramide. Oplophorus luciferase has now been obtained in a highly purified state. Optimum luminescence occurs at pH 9 in the presence of 0.05--0.1 M NaCl at 40 degrees C, and, due to the unusual resistance of this enzyme to heat, visible luminescence occurs at tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 25 publications
4
80
0
1
Order By: Relevance
“…Moreover, it appears that about 30% of its maximum bioluminescence activity is retained at low (10°C) and very high (65°C) temperatures. In the bioluminescence systems of Cypridina, Latia, Chaetopterus, the relative activity decrease steeply when the temperature is raised, and become almost zero at a temperature higher than 40°C [23]. From the Arrhenius plots (inset of Fig.…”
Section: Temperature and Ph Effect On Enzyme Activity And Stabilitymentioning
confidence: 96%
“…Moreover, it appears that about 30% of its maximum bioluminescence activity is retained at low (10°C) and very high (65°C) temperatures. In the bioluminescence systems of Cypridina, Latia, Chaetopterus, the relative activity decrease steeply when the temperature is raised, and become almost zero at a temperature higher than 40°C [23]. From the Arrhenius plots (inset of Fig.…”
Section: Temperature and Ph Effect On Enzyme Activity And Stabilitymentioning
confidence: 96%
“…Previously, the molecular weight of Oplophorus luciferase was reported to be 130 kDa (by gel ¢ltration) for the native protein, and 31 kDa after treatment with SDS [3]. In our recent study, the luciferase showed a molecular weight of approximately 106 kDa in gel ¢ltration, and we found that the molecule breaks down into 35 kDa and 19 kDa proteins upon sodium dodecyl sulfate^polyacrylamide gel electrophoresis (SDS^PAGE) analysis.…”
Section: Introductionmentioning
confidence: 77%
“…Puri¢cation and amino acid sequence analysis of native Oplophorus luciferase A puri¢ed preparation of Oplophorus luciferase obtained in 1978 [3] was further puri¢ed by two steps of chromatography. The ¢rst step was by hydrophobic interaction chromatography on a column of butyl Sepharose 4 Fast Flow (Pharmacia; 0.7U3.5 cm) using 20 mM Tris^HCl, pH 8.5, eluting with decreasing concentrations of ammonium sulfate starting at 1.5 M. The second step was by gel ¢ltration on a column of Superdex 200 Prep (Pharmacia; 1U48 cm) in 20 mM Tris^HCl, pH 8.0, containing 50 mM NaCl.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations